The impact of website quality on customer satisfaction and eWOM in online purchase intention: The moderating role of gender in risk-taking - Saleem, Uzman; yi, Su; Bilal, Muhammad; Topor, Dan Ioan; Căpuṣneanu, Sorinel (Frontiers in Psychology, 2022)
Recently, social media marketing has become one of the most significant growth channels for many businesses. However, many companies are still unclear about using social media marketing to their advantage, particularly in an e-commerce environment. In this background, this study examines the effect of website quality, consumer satisfaction, and eWOM on online purchase intention. An online survey was conducted with 789 online Chinese shoppers from four cities—Harbin, Shenyang, Guangzhou, and Shenzhen. Structural equation modeling (SEM) was used to analyze the hypotheses. The findings show that each variable had a high impact on eWOM with website quality (information quality, system quality, and service quality), which in turn positively increased consumer online purchase intentions in China's e-commerce business. Additionally, findings show a significant gender gap in online shopping behavior. This novel research provides several managerial guidelines that support managers in improving their business performance in the e-commerce industry. This research also highlighted some limitations.